Analysis of the divergences in the nonsense-mediated mRNA decay mechanism among two globin transcripts highly conserved - Pereira, Francisco JC (2012)
Nonsense-mediated mRNA decay (NMD) is a surveillance pathway that recognizes and selectively degrades mRNAs carrying premature termination codons (PTCs, or nonsense codons), which has been highly conserved during evolution. Knowing that human a- and b-globin genes descend from a common ancestral, the aim of this work was to understand if both encoded mRNAs carrying a nonsense mutation, share parallel NMD profiles. We have previously shown that human b-globin mRNAs carrying a PTC located in close proximity to the translation initiation AUG codon escape NMD. This was called the “AUG-proximity effect”. The present work illustrates that the extension of the AUG-proximity effect, i.e. to what position in the open reading frame (ORF) an AUG-proximal PTC does not trigger NMD, is different between human a- and b-globin mRNAs. Remarkably, our data also demonstrate that, contrary to what occurs in the b-globin transcripts, a-globin mRNAs carrying an AUG-proximal PTC allow for efficient translation re-initiation, although it only partially explains their NMD resistance. In addition, our results reveal that in the a- and b-globin transcripts, the extension of the AUG-proximity effect is determined by the ORF sequence. Furthermore, we show how the mRNA secondary structure, which is affected by the ORF sequence, determines the AUG-proximity effect extension. Our data point out that the time taken to translate the short ORF, affected by its sequence and stability, besides being involved in modulating translation re-initiation, also plays an important role in establishing the extension of the AUG-proximity effect. Thus, although both mRNAs are evolutionarily related they show different features in their NMD response.